Quantitative Determination of Ketoprofen Bulk Drug Using Sodium Salt of Aspirin as Hydrotropic Solubilizing Agent - Maheshwari, R.K.; Singh, Mahaveer (Asian Journal of Chemistry, 2010)
In the present investigation, ketoprofen (a widely used non-steroidal antiinflammatory drug) has been selected as a poorly water-soluble model drug. There was more than 50 folds enhancement in aqueous solubility of ketoprofen by 1.0 M aspirin sodium compared to its aqueous solubility. This hydrotropic agent was employed to solubilize the ketoprofen in bulk drug form. The proposed method is new, simple, accurate, environmentally friendly and reproducible. Statistical data proved the accuracy reproducibility and the precision of the proposed method.